Static Rest Frame to Improve Postural Stability in Virtual and Augmented Reality - Shahnewaz Ferdous, Sharif Mohammad; Chowdhury, Tanvir Irfan; Arafat, Imtiaz Muhammad; Quarles, John (Frontiers in Virtual Reality, 2021)
Many users have shown increased postural instability while using Head-Mounted Displays (HMDs) as HMDs block their real-world vision. People with balance impairments are especially more affected by this as they depend more on their visual cues to maintain their balance. In addition, balance is a good indication of cybersickness according to postural instability theory. In this research, we have investigated how to use additional visual cues to improve postural stability. Through conducting one user study in Virtual Reality (VR) and Augmented Reality (AR), we have studied the effect of a Static Rest Frame (SRF) on postural stability in persons with balance impairments due to Multiple Sclerosis (MS). Results indicate that an SRF significantly improves postural stability in VR and AR for users with MS. Based on these results, we propose guidelines for designing more accessible VR and AR systems for persons with balance impairments.